Topology optimization of rigid interlocking assemblies. (1st July 2021) - Aharoni, Lior; Bachelet, Ido; Carstensen, Josephine V.
Highlights: Topology optimized framework for design of multiple rigid interlocking components. Both insertion compatibility and a simplified force interaction are considered. Includes demonstrations on two- and four-component assemblies. Provides extension that adds holes to the designs. Abstract: This paper presents a new density-based topology optimization algorithm for the design of constructible rigid interlocking assemblies with multiple components. The multiple components or structural parts are introduced by having multiple sets of design variables: one for each component. These are filtered separately and combined to create a density field for each structural part. In addition, the framework uses a series of filtering operations to ensure sufficient blocking of rigid body motion and sufficient assemblability. Since this type of assembly is frequently constructed both with and without the use of mortars or adhesives, the structural performance is simplified into a set of static load cases in which the inter-component interactions are estimated. The framework is demonstrated on design examples with two and four components and found to achieve interlocking, constructible assemblies. Crisp interface boundaries and interaction loads along the component interfaces are observed for all examples. Additionally, the two-component solutions are analyzed and compared using computational contact analyses to investigate the influence of the user defined parameters. Finally, an extension is suggested that allows the inclusion of a void phase.